Complex Dispersal of Adult Yellowfin Tuna From the Main Hawaiian Islands - Lam, Chi Hin; Tam, Clayward; Kobayashi, Donald R.; Lutcavage, Molly E. (Frontiers in Marine Science, 2020)
Local availability of yellowfin tuna, Thunnus albacares, is a key economic, dietary and cultural concern for Main Hawaiian Islands (MHI) communities and insular fisheries. Consequently, interactions of inshore versus offshore fisheries and connectivity to yellowfin elsewhere in the Pacific remain important scientific management questions. Local fisheries target adult tuna during the summer months, but subsequent tuna movements, presumably away from the islands after reproduction ceases, remain undocumented. From 2014-2016, we partnered with local fishermen to catch and release nineteen yellowfin tuna (41- 91 kg, estimated whole weight) off Kauaʻi, with popup satellite archival tags programmed for 9 to 12-month missions. Although data collection periods did not exceed 59 days mainly because of tag hardware failures and predator interactions, short tracks revealed diverse patterns: local residency for some individuals, and rapid, long-distance (>800 km) dispersals in multiple directions for others. Adult yellowfin tuna frequenting the MHI have more complex movements than previously assumed. Despite being a nursery area, whether the assemblage is entirely produced and retained in the region is not resolved. However, attaining one-year migration records requires tag performance that was not achieved by the deployed tags. It remains a prerequisite for greater understanding of yellowfin in the Main Hawaiian Islands and Central North Pacific, including assessment of their spatial connectivity, impacts of climate change, and shifting ecosystems.